THE USE OF CAKE APPLICATION ON STUDENTS' SPEAKING SKILL IN ENGLISH FOR SPECIFIC PURPOSES (ESP) - Chusnul Chotimah (Lingua, 2022)
In a digital era, utilizing techonology as a learning media is important things. As mentioned earlier, there are several applications to improve students' speaking skill, one of them is cake application. Speaking is one of the most important skills in learning English and a skill practiced in speaking is how to pronounce words properly and correctly. The purpose of this research is to know the use of cake application as an improvement students’ speaking skill in English for Specific Purposes (ESP). The participant are 33 college students of As-Syafi’iyah Islamic University. This research used qualitative methods and using questionnaire created using google forms and distributed via WhatsApp as the instrument to the students . From the answer of questionnaires can be conclude that students got new word with correct pronunciation and can speak fluently in ESP.